Mandibular densitometric analysis and skeletal dual energy x-ray absorptiometry in osteoporotic females - Hend Mohamed Abuelyazeed; Mohamed Mohamed Elsorougi; Mushira Mohamed Abdellattif Dahaba; Rasha Mohamed Kamal Eldin (Cairo : Hend Mohamed Abuelyazeed, 2010)
The objective of this study was to evaluate the mandibular and skeletal changes in postmenopausal females using densitometric analysis and dual energy x-ray absorptiometry (DXA). Bone mineral density was assessed using DXA in 24 postmenopausal Egyptian females and categorized into three groups, the mandibular bone density and morphometric analysis also were assessed including: mandiblar cortical thickness (MCT), panoramic mandibular index (PMI) and alveolar resorption crest degree M/M ratio
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral-Radiology
Issued also as CD
Keywords: Bone mineral density; Dual energy x-ray absorptiometry; Osteoporosis